If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(3a + -9) = (-3x + 11) Reorder the terms: f(-9 + 3a) = (-3x + 11) (-9 * f + 3a * f) = (-3x + 11) Reorder the terms: (3af + -9f) = (-3x + 11) (3af + -9f) = (-3x + 11) Reorder the terms: 3af + -9f = (11 + -3x) Remove parenthesis around (11 + -3x) 3af + -9f = 11 + -3x Solving 3af + -9f = 11 + -3x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9f' to each side of the equation. 3af + -9f + 9f = 11 + 9f + -3x Combine like terms: -9f + 9f = 0 3af + 0 = 11 + 9f + -3x 3af = 11 + 9f + -3x Divide each side by '3f'. a = 3.666666667f-1 + 3 + -1f-1x Simplifying a = 3.666666667f-1 + 3 + -1f-1x Reorder the terms: a = 3 + 3.666666667f-1 + -1f-1x
| 4=4n-2n | | 2(1.5z+3.5)=16.0 | | P×3/10=3/4 | | 10=6a+4a | | 4x/13=5/2 | | 4(2.1z+2.75)=-14.2 | | 3x+ky=5 | | 8=3n+4+4 | | 1000-r=99.52 | | (3x+y)=(2x+y) | | 0=6cos(x) | | 2(6x+4)=44 | | 12=4k+6+2k | | 1931+x=4734 | | 2+y=4-6 | | 26-5-12+6= | | 6(r-4)-5r=-13+2 | | 5x/3=8/3 | | (6y+1)=(4y+9) | | x^2-2x+1.3=0 | | 5x-4x+13=13-4 | | 3x(8x+15)=180 | | 2x-2(x-5)=126 | | 4(x-5)+2(x-6)=62 | | 65=3w+8 | | -6*sin(x)=0 | | 3x-6+2x=78 | | 0=-6sin(x) | | 31=-8v-1 | | 54v^3+2= | | 16=20+5(x-2.8) | | 10=6x-4-5x |